Learning HCI from a Virtual Flipped Classroom: improving the students' experience in times of COVID-19 - Martinelli, Suéllen R.; Zaina, Luciana A. M. (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2021)
Human-Computer Interaction Learning (HCI) experiences have been carried out to investigate approaches that can motivate and assist higher education students in their teaching-learning process. Due to the COVID-19 pandemic, higher education professors have faced many challenges to adapt their classes to the online mode. The literature about HCI education experiences fully online is still scarce. This paper aims to present a Virtual Flipped Classroom-based approach conceived to be applied to teaching HCI to undergraduate and graduated students. We designed our approach taking into account a blended strategy that splits the learning process into two distinct moments called out of class and in-class, even they are carried out virtually. We also included in our approach the use of active methodologies (e.g. Project-based learning, Problem-based learning). We evaluate our approach by collecting the students’ experience in the middle and at the end of the HCI course based on a questionnaire and interviews, respectively. The results revealed that the students had a high level of satisfaction, motivation and feeling that they learned about the out of class materials and in-class hands-on activities. In an in-depth qualitative analysis of students answers from the questionnaire and the interviews, nine positive aspects raised against five negative aspects regarding our approach. The mindset changing about the importance of HCI knowledge in their daily work and the students’ motivation about the course design were positive aspects. We concluded that the shaping of classes split out of class and in-class moments promote the students’ autonomy and collaboration, even with all the challenges they faced in times of COVID-19.